(untitled) (International Journal of Current Engineering and Technology, 2015)
In today’s world of economic and social industry there exists an over demand and rising need of information. Due to which a problem of storage and maintaining big data comes into picture. It is challenging task to manage and retrieve relevant information from big data. This data basically has storage memory in terabyte and petabyte hence becoming it difficult to process and analyze. The specified project basically uses Hadoop, a tool specified by Apache Server, for information retrieval. Hadoop is a Java Software Framework that supports data intensive distributed applications and is developed under open source license. Many websites including Facebook and Twitter rely on Hadoop. The two major pieces of Hadoop are HDFS and MapReduce. In this paper we are focusing on MapReduce technique, one of the most common techniques used for retrieval of information.